Combination of Biochar and Polyurethane Media in a Series-Connected Filtration Column for Microplastic Removal and Effluent Toxicity Testing - Tivany Edwin; Budhi Primasari; Vera Surtia Bachtiar; Juwita Pratiwi; Ulya Afifah (Indonesian Journal of Environmental Management and Sustainability, 2026)
This study aimed to evaluate the efficiency of microplastic removal using filtration media composed of coconut shell biochar and polyurethane sponge, as well as to assess the potential toxicity of the filtered water on feed consumption efficiency in Oreochromis niloticus and microplastic bioaccumulation by fish. The filtration system had a diameter of 10 cm, employed an upward flow configuration, and operated at a flow rate of 30 mL/min. Optimization was conducted using an artificial solution containing microplastics through two series-connected filtration columns with a media thickness of 40 cm. Toxicity tests on the filtered water were performed on Nile tilapia using feed efficiency and the fish’s bioaccumulation capacity of microplastics as parameters, with fish sized 4-5 cm. Results showed that the highest microplastic removal efficiency for the first and second filter averaged 79% and 93%, respectively. Toxicity tests based on feed efficiency showed favorable percentages in experiments using the effluent from the second series column filter compared to the first series, even though the fish feed efficiency of both water effluent decreased on day 14. The highest microplastic accumulation was observed in the digestive tract, followed by the fish gill and fish muscle, respectively. The bioaccumulation factor (BAF) value of microplastic in fish was less than 1, indicating a low level of bioaccumulation. This study demonstrates that the combination of coconut shell biochar and polyurethane sponge in two series of filtration has strong potential as an effective, economical, and accessible solution for microplastic filtration in water treatment.